The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/jpepsy/jsu008
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Psychological Therapies for Children With Chronic Pain

Abstract: Evidence for psychological therapies treating chronic pain is promising. Recommendations for clinical practice and research are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
176
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 272 publications
(186 citation statements)
references
References 78 publications
7
176
0
3
Order By: Relevance
“…Another review of psychological treatment of headaches concluded that higher treatment dose leads to better pain scores posttreatment. 38 The studies included in this review delivered biofeedback in a clinic, which is time-consuming for the patient and hampers the widespread delivery of treatment, despite its positive results in treating headache. This finding has led to the emergence of less time-consuming approaches, such as prudent limited office treatment and Internet-based delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Another review of psychological treatment of headaches concluded that higher treatment dose leads to better pain scores posttreatment. 38 The studies included in this review delivered biofeedback in a clinic, which is time-consuming for the patient and hampers the widespread delivery of treatment, despite its positive results in treating headache. This finding has led to the emergence of less time-consuming approaches, such as prudent limited office treatment and Internet-based delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews highlight the effectiveness of psychological therapies for the treatment of chronic pain in youth, 14,15 but no reviews have examined the benefits of IIPT, despite the growing need for and interest in this particular form of treatment. In addition, although we know the components of IIPT programs for youth with chronic pain are diverse, no previous studies have systematically examined the programs and described the treatments.…”
mentioning
confidence: 99%
“…The changes that occur in chronic pain to the entire central nervous system and brain do not differentiate in any way between, for instance, the individual with diagnosed osteoarthritis or the individual with joint pain but no X-ray findings, nor between the individual with celiac disease and another with irritable bowel syndrome. 48 Although much research and clinical effort have focused on adults of working age with chronic pain, CBT has been applied to help children 18,49 and older adults, 50 and to those with pain at the end of life. [51][52][53][54] We suspect that clinicians and researchers will continue to apply the general principles of CBT to a wide range of pain-related disorders.…”
Section: Likely Developments and Challengesmentioning
confidence: 99%